Data Preprocessing: Case Study on monthly number of visitors to Taiwan by their residence and purpose - Muhammad Reza Putra; Azuraliza Abu Bakar (Universitas Putra Indonesia YPTK Padang, 2020)
This paper will explain in details on data reports preliminary on dataset, how the pre-processing data mainly for data cleaning and reduction process applied to a dataset. The dataset that will be used is number of visitors to Taiwan by their residence and purpose.Dataset which is obtained based on kaggle, findings from Scraped from Taiwan Tourism Bureau. The surveys have been carried out using Foreign visitor data covers all foreign visitors directly arrived in Taiwan through the airports, ports and land.